Adaptation and correlated fitness responses over two time scales in Drosophila suzukii populations evolving in different environments. (2nd July 2021) - Olazcuaga, Laure; Foucaud, Julien; Gautier, Mathieu; Deschamps, Candice; Loiseau, Anne; Leménager, Nicolas; Facon, Benoit; Ravigné, Virginie; Hufbauer, Ruth A.; Estoup, Arnaud; Rode, Nicolas O.
Abstract: The process of local adaptation involves differential changes in fitness over time across different environments. Although experimental evolution studies have extensively tested for patterns of local adaptation at a single time point, there is relatively little research that examines fitness more than once during the time course of adaptation. We allowed replicate populations of the fruit pest Drosophila suzukii to evolve in one of eight different fruit media. After five generations, populations with the highest initial levels of maladaptation had mostly gone extinct, whereas experimental populations evolving on cherry, strawberry and cranberry media had survived. We measured the fitness of each surviving population in each of the three fruit media after five and after 26 generations of evolution. After five generations, adaptation to each medium was associated with increased fitness in the two other media. This was also true after 26 generations, except when populations that evolved on cranberry medium developed on cherry medium. These results suggest that, in the theoretical framework of a fitness landscape, the fitness optima of cherry and cranberry media are the furthest apart. Our results show that studying how fitness changes across several environments and across multiple generations provides insights into the dynamics of local adaptation that would not be evident if fitness were analysed at a single point in time. By allowing a qualitative mapping of an experimental fitness landscape, our approach will improve our understanding of the ecological factors that drive the evolution of local adaptation in D . suzukii . Abstract : Using fitness landscape theory to study adaptation and correlated fitness responses over two time scales in Drosophila suzukii populations evolving in different fruit environments.